Sedekah Sebagai Kekuatan Spiritual (Studi Kasus pada Komunitas Yuk Sedekah Bandung) - Dewi Mariyana; Naan Naan; Tamami Tamami (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2019)
Many societies are moslem, but some of them don’t want to give alms. Their reason don’t give alms because they wait for rich. Actually the alms doesn’t have to wait for to be rich, but is difficult condition also Allah suggests to give the alms. This research is done to know the alms existential in Yuk Sedekah Bandung community. And, to know spiritual valeu which form giving alms in teh Yuk Sedekah Bandung community. The method is used in this observation is descriptive qualitative, it’s the method which describes of gives imagination about event which is observed completly (not only something is looked and suppressed). In order to produce the deepest meaning. It’s own data source are founding, director, members and donors Yuk Sedekah Bandung community. The result of this research show that: (1) the existential of alms is looked at from alms implementation proces in the Yuk Sedekah Bandung community is done with theree fixed program of community, they are Yuk Sedekah Bank, Yuk Sedekah Berbagi and Yuk Sedekah Berbakti. While the alms support factor in this community there are inspiration, motivation, massage, empathy excessive treasures and freetime which is had by the members og Yuk Sedekah Bandung community. And the alms resistor factor in this community are personal necessity, wrong place to give alms and temptation don’t give high alms. (2) spiritual value form from the alms in Yuk Sedekah Bandung community are increasing faith, and it can be responsible it’s own treasure on the judgment day, increasing spirited, knowledge, istiqamah, good manners and as a liaison after praying between the child with parents who has died. Increasing hospitality and happiness between donors with receiver, and expediting matter and sustenance, increasing inner serenity and meaning of life.